THE RELATIONSHIP BETWEEN SELF-CONFIDENCE, SOCIAL INTERACTION, AND LEARNING ACTIVENESS TOWARD MATHEMATICS LEARNING OUTCOMES - Siti Maesaroh; Uus Kusdinar (Universitas Ahmad Dahlan, 2019)
Poor student learning outcomes are associated with many factors. The relationship between self-confidence, social interaction, and learning activeness is possibly related to learning outcomes. This research aims to determine the presence or absence of a positive and significant relationship between self-confidence, social interaction, and learning activeness. Mathematics Learning Outcomes in Students Class VII of State Junior High School (SMP Negeri) 9 Yogyakarta in Even Semester in Academic Year of 2016/2017. The population in this research was the students of VII of SMP Negeri 9 Yogyakarta in the academic year of2016/2017, consisted of class VIIA, VIIB, VIIC, VIID, VIIE, VIIF, totaling 203 students. Samples were taken from VII C as the research sample class and with the random sampling technique. The writer uses the questionnaire method to collect self-confidence, social interaction, and learning activeness and test method to get the resulting math results. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes normality, the test of linearity, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed a positive and significant relationship between self-confidence, social interaction, and learning activeness with mathematics learning outcomes in students class VII of SMP Negeri 9 Yogyakarta in Even Semester in Academic Year of 2016/2017. It is showed by Fcount Ftable is with and with , with , and , dan .